MAPK pathway activation selectively inhibits ASCL1-driven small cell lung cancer - Rebecca Caeser (Elsevier, 2021)
Summary: Activation of mitogenic signaling pathways is a common oncogenic driver of many solid tumors including lung cancer. Although activating mutations in the mitogen-activated protein kinase (MAPK) pathway are prevalent in non-small cell lung cancers, MAPK pathway activity, counterintuitively, is relatively suppressed in the more aggressively proliferative small cell lung cancer (SCLC). Here, we elucidate the role of the MAPK pathway and how it interacts with other signaling pathways in SCLC. We find that the most common SCLC subtype, SCLC-A associated with high expression of ASCL1, is selectively sensitive to MAPK activation in vitro and in vivo through induction of cell-cycle arrest and senescence. We show strong upregulation of ERK negative feedback regulators and STAT signaling upon MAPK activation in SCLC-A lines. These findings provide insight into the complexity of signaling networks in SCLC and suggest subtype-specific mitogenic vulnerabilities.